Cardiovascular Autonomic Responses in the VCD Rat Model of Menopause: Effects of Short- and Long-Term Ovarian Failure. (July 2018) - Huber, Domitila A.; Bazilio, Darlan; Lorenzon, Flaviano; Sehnem, Sibele; Pacheco, Lucas; Anselmo-Franci, Janete A.; Lima, Fernanda B.
After menopause, hypertension elevates the risk of cardiac diseases, one of the major causes of women's morbidity. The gradual depletion of ovarian follicles in rats, induced by 4-vinylcyclohexene diepoxide (VCD), is a model for studying the physiology of menopause. 4-Vinylcyclohexene diepoxide treatment leads to early ovarian failure (OF) and a hormonal profile comparable to menopause in humans. We have hypothesized that OF can compromise the balance between sympathetic and parasympathetic tones of the cardiovascular system, shifting toward dominance of the former. We aimed to study the autonomic modulation of heart and blood vessels and the cardiovascular reflexes in rats presenting short-term (80 days) or long-term (180 days) OF induced by VCD. Twenty-eight-day-old Wistar rats were submitted to VCD treatment (160 mg/kg, intraperitoneally) or vehicle (control) for 15 consecutive days and experiments were conducted at 80 or 180 days after the onset of treatment. Long-term OF led to an increase in the sympathetic activity to blood vessels and an impairment in the baroreflex control of the heart, evoked by physiological changes in arterial pressure. Despite that, long-term OF did not cause hypertension during the 180 days of exposure. Short-term OF did not cause any deleterious effect on the cardiovascular parameters analyzed. These data indicate that long-term OF does not disrupt the maintenance of arterial pressure homeostasis in rats but worsens the autonomic cardiovascular control. In turn, this can lead to cardiovascular complications, especially when associated with the aging process seen during human menopause.